Religious Associations of the Tatarian ASSR During the Khruschev’s Thaw - Galimzyanova, Liliya; Ibragimov, Ruslan; Fazliev, Aivaz; Samatova, Chulpan (Journal of History Culture and Art Research, 2018)
The relevance of this paper is due to the multicultural nature of the Russian state and the significant role of religion in the contemporary socio-cultural and political processes taking place in the country. The knowledge and analysis of the history of the relationship between government and religion in Russia in general and in its individual regions will undoubtedly contribute to a more objective understanding of the fundamental aspects of the contemporary religious situation in Russia, since many problems in this field are now, in many cases, conditioned by a certain specificity or distortions in the state’s policy toward religion - in the past. In this regard, the chronological scope of the research - the ambiguous and in many respects contradictory period of the Khrushchev’s "thaw" - has a great scientific and applied interest in the problems under study. The administrative and geographic scope of the study is limited to the territory of the Tatar ASSR - a region traditionally formed as multi-confessional. At the same time, the processes that took place in the religious sphere of the Tatar ASSR in many respects were characteristic of many other multicultural regions of the Soviet state. The objective of the paper is to identify the factors that conditioned the survival and functioning of religious associations of the republic under the dominating atheistic ideology and strengthening of the anti-religious administrative pressure of the state in the contradictory period of the Khrushchev’s "thaw".